Research in finance. Vol. 23 - Chen, Andrew H. (Emerald, 2006)
This volume contains contributions on a range of important issues in current financial research. Topics included are - the performance of fixed income mutual funds in different economic states, the determinants of long-term excess performance of the ADRs on the NYSE, the models for forecasting the Euro/US Dollar exchange rates and the U.S. mutual funds movements, the fragmentation in day and night markets, the market reactions of the U.S.-listed foreign banks to the passage of the GLB Act of 1999, the upper bounds for American options, the spread-based models for the valuation of credit derivatives, the empirical evidence on the evolution of corporate borrowers, the determinants of private debt source, and the underlying causes and resolution policies for the systematic banking crises. This is a valuable addition to the research of finance. It contains contributions from key figures the world of finance; and offers broad coverage.
Keywords: Finance -- Research.; Banks and banking.; elektronické knihy; electronic books